Sexual and Reproductive Rights: policy and budget under the Temer and Bolsonaro governments - Peixoto, Valdenizia Bento; Salvador, Evilasio; Bianchetti, Ana Luiza (Argumentum, 2023)
Abstract: This article analyses social policies regarding Sexual and Reproductive Rights (SRRs) under the Temer and Bolsonaro governments. It investigates programmes and actions related to the budget for SRRs, in the Pluriannual Plan (PAP) for 2016 to 2019. Bibliographic research was conducted on the overlap between capitalist and patriarchal domination/exploitation systems, the contextualisation of SRRs and analysis of the data collected on the respective governments. It concludes that these social policies were not a priority, with some programmes being officially proposed but barely or never implemented, and an increase in measures counter to previously gained rights. The budget data expresses in financial terms, the setbacks caused by governmental measures that interdict the guarantee of rights and the sexual and reproductive health of women. Keywords: Sexual and Reproductive Rights. Social Policy. Budget.